Hubungan Ketepatan Triase Dengan Keberharhasilan Penatalaksanaan Tindakan Keperawatan Kegawatdaruratan Ruang IGD Di Rumah Sakit Daerah Tulungagung - Manggar Purwacaraka; Rio Ady Erwansyah; Shulhan Arief Hidayat; Farida (PROFESSIONAL HEALTH JOURNAL, 2024)
Emergency is a critical situation that requires prompt action to save lives. Triage in the Emergency Department (ED) is a crucial step in managing patients with emergency conditions. Emergency nurses must possess triage skills both in the pre-hospital phase and within the hospital setting. The success of patient management in the hospital significantly depends on the accuracy of triage implementation. This research aims to determine the relationship between triage accuracy and the success of emergency nursing care management in the ED of Tulungagung Regional Hospital. The study employs a correlational analytic quantitative approach with a cross-sectional design, involving a sample of 52 nurses from both Type B and Type C Hospitals in Tulungagung. Data are analyzed through univariate and bivariate analyses using the Chi-Square Test. The results indicate that out of the total respondents (52 individuals), 38 (73.1%) successfully conducted accurate triage, and 42 (80.8%) succeeded in emergency care management. The statistical test results yield a p-value of 0.000 (Pvalue> 0.05), concluding that there is a significant relationship between triage accuracy and the success of emergency nursing care management in the ED of Tulungagung Regional Hospital. The precision of triage by nurses directly impacts the effectiveness of emergency care management